2019
DOI: 10.1111/jcpe.13179
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of oral inflammation in perinatally HIV‐infected and perinatally HIV‐exposed, uninfected youth

Abstract: Aim To examine oral biomarkers that have been associated with periodontal disease progression in HIV‐infected adults in perinatally HIV‐infected and HIV‐exposed but uninfected youth. Material and Methods This was a cross‐sectional, multicentre substudy of youth participating in the Oral Health Pediatric HIV/AIDS Cohort study. Gingival crevicular fluid repository samples from participants with and without periodontal disease (using Gingival Index [GI] and Bleeding on Probing [BOP] parameters on dental examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…While a wide range of caries prevalence has been reported in school-aged children in sub-Saharan Africa, several studies report estimates ranging 10-22% [11,[31][32][33][34]. Results from several studies of children perinatally infected with HIV, including ours of early childhood [4,20], are consistent with our findings of a higher caries prevalence in HIV-infected children [2,3,8,13,17,18,[35][36][37][38][39][40][41]. While a non-comparative study [42] observed a low prevalence of early childhood caries in children with perinatal HIV infection, several comparative studies [4,13,25,37,43] have reported elevated risk of dentalrelated diseases, including caries, in PLWH compared to their uninfected counterparts.…”
Section: Discussionsupporting
confidence: 89%
“…While a wide range of caries prevalence has been reported in school-aged children in sub-Saharan Africa, several studies report estimates ranging 10-22% [11,[31][32][33][34]. Results from several studies of children perinatally infected with HIV, including ours of early childhood [4,20], are consistent with our findings of a higher caries prevalence in HIV-infected children [2,3,8,13,17,18,[35][36][37][38][39][40][41]. While a non-comparative study [42] observed a low prevalence of early childhood caries in children with perinatal HIV infection, several comparative studies [4,13,25,37,43] have reported elevated risk of dentalrelated diseases, including caries, in PLWH compared to their uninfected counterparts.…”
Section: Discussionsupporting
confidence: 89%
“…Additional studies were excluded in the analysis because the levels of CD14 were not specifically retrieved in human patients, but in human cell cultures obtained from a Research center [48,49] and in vitro dental mesenchymal stromal cells or cell line studies [39]. Furthermore, subsequent reports were not included due to the fact that the tested or the control group were known to be individuals with compromised health (i.e., renal transplant patients [50,51] or HIV [52]. Finally, overview articles [53] and literature reviews of markers in periodontitis [54] provided great general information, but lacked the specificity in providing case control study examples, and thus results as such were excluded as well.…”
Section: Periodontitis Patients;mentioning
confidence: 99%
“…In contrast, little is known about oral mucosal immunity and microbiota, particularly in PLWH. The prevalence of noncommunicable diseases, including caries (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), mucosal inflammation (18), gingivitis (18)(19)(20), periodontal disease (21)(22)(23), and oral mucosal inflammation in general (24,25), is higher in PLWH than in uninfected individuals, suggesting a heightened susceptibility to multifactorial chronic inflammation that would compromise the integrity of tooth-supporting tissues. The disruption of host-microbe homeostasis in oral epithelial tissues contributes to disease progression of gingival and periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%